2014
DOI: 10.1186/s12711-014-0065-5
|View full text |Cite
|
Sign up to set email alerts
|

Two recessive mutations in FGF5 are associated with the long-hair phenotype in donkeys

Abstract: BackgroundSeven donkey breeds are recognized by the French studbook. Individuals from the Pyrenean, Provence, Berry Black, Normand, Cotentin and Bourbonnais breeds are characterized by a short coat, while those from the Poitou breed (Baudet du Poitou) are characterized by a long-hair phenotype. We hypothesized that loss-of-function mutations in the FGF5 (fibroblast growth factor 5) gene, which are associated with a long-hair phenotype in several mammalian species, may account for the special coat feature of Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Hair growth was considered to be regulated by hairless gene, FOXI3 13, hypertrichosis gene, FGF13, Trps1, Sox9 1415, and hair overgrowth gene, ABCA5 16. However, natural long hair, well described angora phenotype, results from a regulator gene, FGF5 , in many kinds of mammals1718192021. Here FGF5 have been included in the candidate genes sets based on low heterozygosity and high genetic differentiation in IMCG population (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hair growth was considered to be regulated by hairless gene, FOXI3 13, hypertrichosis gene, FGF13, Trps1, Sox9 1415, and hair overgrowth gene, ABCA5 16. However, natural long hair, well described angora phenotype, results from a regulator gene, FGF5 , in many kinds of mammals1718192021. Here FGF5 have been included in the candidate genes sets based on low heterozygosity and high genetic differentiation in IMCG population (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of the wool traits of the targeted founders indicated that GM sheep with loss‐of‐function modifications exhibited an increase in wool staple length, wool stretched length and grease fleece yield. The improvement of wool traits is in agreement with long‐haired phenotypes that were previously observed in spontaneous loss‐of‐function mutations of FGF5 in mice and donkeys , as well as in targeted dysfunctional modification in FGG5 knockout Dorper sheep . Overall, we deduced that the targeted effect most possibly resulted from loss‐of‐function modifications of the FGF5 gene because of a lack of the β‐strand domain of mutant FGF5.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Przewalski horses (Equus przewalskii) (Yasinetskaja 1999) and Polish Konik horses (Stachurska et al 2007) showed that the coat cover hairs are thinner in winter than in summer. This phenomenon may be due to hormone changes induced by day length increase in the spring, causing hair follicles to enter catagen (regressive phase of the hair cycle) and telogen (dormancy) (Nixon et al 2002, Legrand et al 2014). On the other hand, in the summer, nutrition is richer and more differentiated than in winter, which can increase the horse hair thickness.…”
Section: Introductionmentioning
confidence: 99%